Nos Sertões coloniais do Ararobá: Garanhuns, da povoação à vila. - Gonçalves, Ígor Anderson Cardoso (2023)
This research intends to analyze the trajectory of the Brazilian community of Garanhuns, in the State of Pernambuco, from when the Portuguese started to be present in that region, then called Sertao do Araroba, to be conquered to the indigenous and “quilombolas” in the 17th century, and integrated into its administrative order; until the achievement of its political autonomy in the beginning of the 19th century, when the municipality was properly created and installed. The study, however, transcends the apparently local and restricted contours of the object, concerning what the most recent historiography is calling “miniaturized political spaces”, not yet properly examinated in the academic field. Thus, comparing diverse sources, many of which still unexplored, some lesser known dimensions of the local power are scrutinized, in order to clarify the subject from the case of Garanhuns. As a product, the first chapters of an auxiliary book in preparation are already presented to the public.